Task, Firm Size, and 0rganizational Structure in Management Consulting An Empirical Analysis from a Contingengy Perspective - Graubner, Michael (ebs-Forschung, Schriftenreihe der EUROPEAN BUSINESS SCHOOL Schloß Reichartshausen, 2006)
The management consulting industry has grown into a sizeable economic sector and employment market. Globally operating consulting firms, with thousands of consultants, have emerged. They coexist alongside many small consultancies and single practitioners. As a result, a remarkable diversity in the organizational structure of consulting firms has developed. Organizational structure is of utmost importance for consultancies as it directly impacts their business and employment models. Yet, little scientific explanation has been offered so far on the factors accounting for the diversity of organizational structure in management consulting. Michael Graubner uses the contingency theory of organizations to investigate consultancies' organizational structure in terms of structural differentiation, specialization, centralization, and formalization. He analyzes extensive qualitative and quantitative data obtained during a series of personal interviews in consulting firms with offices in Germany, Austria, and Switzerland. The results show that organizational size and to a lesser degree task uncertainty are closely associated with organizational structure.